Study of the role of Friedel's salt on anions under different pH - Wong, Shook Leng. (2008)
The objective of this research is to study the stabilising capability of Friedel’s salt on anionic heavy metals present in municipal solid waste (MSW) incineration fly ash. The stabilising capability is in terms of the sorption property of Friedel’s salt under different pH. In this research, chromate, dichromate, selenate and vanadate undergo several laboratory tests. Chromate was subjected to pH 7 and 10; dichromate was tested under pH 4, while selenate and vanadate were tested using pH 4, 6, 8 and 10. The sample of synthetic Friedel’s salt used in the study was obtained from an oversea university. Sorption laboratory tests were conducted to determine the effect of initial heavy-metal concentration and pH level on sorption kinetics. Desorption laboratory tests were also carried out to investigate the stability of sorbed heavy metals on Friedel’s salt. The processed liquid (or supernatant) obtained after sorption and desorption was tested to determine the sorption density of Friedel’s salt, the chloride concentration, and pH level. On the other hand, the processed solids were tested for changes in composition and chemical bonding of the Friedel’s salt structure.